Effect of salt solution wet-dry cycling on the bond behavior of FRP-concrete interface. (10th September 2020) - Wang, Y.L.; Guo, X.Y.; Shu, S.Y.H.; Guo, Y.C.; Qin, X.M.
Highlights: Behavior of FRP-to-concrete interface degraded after salt solution wet-dry cycles. Debonding load was derived based on the degradation of FRP-to-concrete interface. Stiffness of FRP-to-concrete interface degraded obviously. Durability of BFRP-to-concrete interface was weaker than that of CFRP. Abstract: The strengthening of concrete structures with externally bonded fiber reinforced polymer (FRP) was increasingly being used in marine exposure environments. Marine environment exposure may significantly affect the bonding behavior of FRP externally bonded to concrete. This paper is intended for studying the effect of tidal-like condition such as salt solution wet-dry cycling on the behavior of FRP-concrete interface. Exposure tests and analytical approach are carried out on specimens externally bonded with carbon fiber reinforce polymer (CFRP) and basalt fiber-reinforce polymer (BFRP). Test variable include the types of fiber and the environmental exposure periods (0, 90, 180, 270, 360 cycles). From the bending test results, the bilinear bond stress-slip relationships for different exposure periods are derived. Based on these bond stress-slip relationships, the full-range behavior of shear stress along the bond length and debonding load can be obtained through the analytical solution. The test and numerical results show that salt solution wet-dry cycling can greatly affect the bond behavior of CFRP-concrete and BFRP-concrete interface with the increase of exposure periods. With the increase of exposure periods, the position of maximum shear stress tend to move backward, which indicates the behavior of FRP-concrete interface is weakened due to the salt solution wet-dry cycling. Compared with CFRP-concrete interface, salt solution wet-dry cycling exposure has greater influence on the bond behavior of the BFRP-concrete interface.